2019
DOI: 10.15388/omee.2019.10.18
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Ownership and Stock Return Volatility in Vietnam: the Destabilizing Role of Firm Size

Abstract: This study aims to examine the relevance of foreign ownership to stock return volatility in the Vietnam stock market over ten years (2008 -2017). After applying the fixed effects regressions and the extended instrumental variable regressions with fixed effects, we find that foreign ownership decreases the volatility of stock returns. However, the stabilizing impact of foreign ownership on stock return volatility becomes weaker in large firms since the coefficient of the interaction term between firm size and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In addition, we found a negative link between firm size and risk. This may be because large companies, which enjoy better governance and less information asymmetry, tend to control the volatility of stock returns [57]. This negative relationship was also found by Damanpour [58] who argues that large companies better control fluctuations in stock prices.…”
Section: Corporate Governance -Recent Advances and Perspectivesmentioning
confidence: 66%
“…In addition, we found a negative link between firm size and risk. This may be because large companies, which enjoy better governance and less information asymmetry, tend to control the volatility of stock returns [57]. This negative relationship was also found by Damanpour [58] who argues that large companies better control fluctuations in stock prices.…”
Section: Corporate Governance -Recent Advances and Perspectivesmentioning
confidence: 66%
“…Social media platforms make obtaining information cheap and easy. The dynamic network effects of social media help reach a potential group of investors that were not easily reachable through traditional media, as highlighted by To et al (2019).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the prior literature on Vietnamese firms, there are a limited number of studies on the nexus between foreign ownership and the price volatility of financial firms in Vietnam. To our best knowledge, all existing literature on Vietnamese firms conclude that an increasing foreign ownership status induces a negative impact on stock return volatility [6,8,11] , implying that the market seems to be more stable with the active participation of foreign investors. Specifically, Vo [11] investigating the case of an developing ecnomy by using a detailed panel data set of firms listed on stock exchange for the period from 2006 to 2012 showed that firm ownership by foreign investors decreased firm stock price volatility in the Vietnam stock market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This raises a concern to identify factors affecting the volatility of those influential stocks. Foreign ownership has been considered as one of the factors impacting stock return volatility recently stated by many authors [1][2][3][4][5][6][7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation